Taxation under oligopoly in a general equilibrium setting - David R. Collie (Cardiff University, Cardiff Business School, 2015)
Taxation under oligopoly is analysed in a general equilibrium setting where the firms are large relative to the size of the economy and maximise the utility of their shareholders. It turns out that the model is an aggregative game, which simplifies the comparative statics for the effects of taxation. This novel analysis of taxation leads to a number of counterintuitive results that challenge conventional wisdom in microeconomics. A lump-sum tax may increase the price of the oligopolistic good and decrease welfare whereas a profits tax may decrease the price of the oligopolistic good and increase welfare. An ad valorem tax may decrease the price of the oligopolistic good and increase welfare. Furthermore, in line with conventional wisdom, total tax revenue is always higher with an ad valorem tax than with a specific tax that leads to the same price for the oligopolistic good.
Keywords: C72; D21; D43; D51; H22; H25; L13; L21; 330; Oligopoly; General Equilibrium; Aggregative Games; Ad Valorem Taxes; Specific Taxes; Profits Taxes; Lump-Sum Taxes